HUBUNGAN DUKUNGAN KELUARGA DENGAN KEKAMBUHAN PADA PENDERITA SKIZOFRENIA DALAM HAL MENGKOMSUMSI OBAT - Simbolon, Helen Emsita; Sitompul, Donald F; Hutasoit, Eka S.P. (Universitas Methodist Indonesia, 2021)
Background: Adherence to taking medication is a behavior that must be followed by outpatient schizophrenia patients to minimize relapse. But unfortunately, many sufferers do not regularly take medication, one of which is due to lack of support from their family and environment for themselves, as well as because of the side effects of drugs for sufferers. Method : This type of research is a study using the literature method or (literaure review). Result : The resultshowed that there was a relationship between family support and relaps in schizophrenicpatients in terms of taking medication. Conclusion: From 15 research journals, there are 13 journals that have a relationship between family support and relapse of schizophrenic patients. There are 9 journals that have a relationship between medication adherence and relapse of schizophrenic patients.